2014
DOI: 10.1002/aenm.201301875
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalysis for Hydrogen Evolution Reactions from WS2 Nanoribbons

Abstract: A facile route is developed to boost the electrocatalytic activity of WS2 by chemically unzipping WS2 nanotubes to form WS2 nanoribbons (NRs) with increased edge content. Analysis indicates that the hydrogen evolution reaction activity is strongly associated with the number of exposed active edge sites. The formation of WS2 NRs is an effective route for controlling the electrochemical properties of the 2D dichalcogenides, enabling their application in electrocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 34 publications
3
100
0
Order By: Relevance
“…The much lower Tafel slope of NPG/WSx indicates the lower HER activation energy and better electrical conductivity between the active sites of WS x . The Tafel slope of 74 mV dec -1 for NPG/WS x is much lower than that of WS 2 particles on Toray carbon paper (135 mV dec -1 ) 41 , and comparable to that of WS 2 nanosheet obtained from ball-milling (72 mV dec -1 ) 42 , WS 2 nanoribbons by chemically unzipping WS 2 nanotubes (68 mV dec -1 ) 12 , WS 2 particles on carbon cloth (78 mV dec -1 ) 30 and graphene film-confined WS 2 nanoparticles (67 mV dec -1 ) 43 .…”
Section: Electrochemical Measurementsmentioning
confidence: 82%
“…The much lower Tafel slope of NPG/WSx indicates the lower HER activation energy and better electrical conductivity between the active sites of WS x . The Tafel slope of 74 mV dec -1 for NPG/WS x is much lower than that of WS 2 particles on Toray carbon paper (135 mV dec -1 ) 41 , and comparable to that of WS 2 nanosheet obtained from ball-milling (72 mV dec -1 ) 42 , WS 2 nanoribbons by chemically unzipping WS 2 nanotubes (68 mV dec -1 ) 12 , WS 2 particles on carbon cloth (78 mV dec -1 ) 30 and graphene film-confined WS 2 nanoparticles (67 mV dec -1 ) 43 .…”
Section: Electrochemical Measurementsmentioning
confidence: 82%
“…42 A small Tafel slope will be beneficial in practical applications, because it will result in a strongly enhanced HER rate at a moderate increase of overpotential. 43,44 Meanwhile, as an important parameter describing HER activity of a catalyst, the exchange current densities of WS 2 , WSe 2 , and WS 2(1Àx) Se 2x NTs are determined to be 0.012, 0.003, and 0.029 mA cm À2 by fitting the linear portion of the Tafel plot at low cathodic current to the Tafel equation.…”
Section: Articlementioning
confidence: 99%
“…Among the newly discovered catalysts, two-dimensional layered transition metal dichalcogenides (TMDs) have emerged as promising electrocatalysts for HER. [8][9][10][11][12] In TMDs, molybdenum disulfide (MoS 2 ) has shown to be an excellent HER catalyst. 8 The computational and experimental results confirmed that the active catalytic sites of layered MoS 2 crystals are located at the sulfur edge, while basal planes are catalytically inert.…”
Section: Introductionmentioning
confidence: 99%